Lecturer Welfare and Learning Quality in Higher Education Management: A Study at Satya Wiyata Mandala University Nabire - Lamba Toding Palimbu; Kristoforus Mikhael Bouk (Lembaga Publikasi Ilmiah Nusantara, 2026)
Lecturer welfare constitutes a strategic component of human resource management in higher education institutions, particularly in private universities that face structural and financial constraints. From a higher education management perspective, adequate lecturer welfare is important for strengthening academic motivation, professional commitment, and the effectiveness of the learning process. This study aims to analyze the role of lecturer welfare in improving learning quality at Satya Wiyata Mandala University (USWIM), Nabire, Central Papua. The study employed a qualitative descriptive approach to obtain an in-depth understanding of lecturers' perceptions and institutional conditions. Data were collected through interviews, observations, and document analysis involving lecturers from several study programs at USWIM Nabire. The findings reveal that lecturer welfare encompasses both material aspects, including basic salary, professional allowances, and performance incentives, and non-material aspects such as job satisfaction, work environment, leadership support, and opportunities for professional development. These factors significantly influence lecturers' motivation, professionalism, and engagement in fulfilling the tridharma of higher education, ultimately affecting the quality of learning. Improved lecturer welfare encourages more innovative teaching practices, stronger lecturer–student interaction, and more effective learning management. The study also highlights the importance of institutional policies that prioritize lecturer welfare as a strategic element of higher education management. Such policies are essential for maintaining academic stability and improving learning quality in private universities, particularly in geographically and economically constrained regions such as Central Papua. The findings provide practical implications for higher education administrators in designing sustainable welfare policies to strengthen institutional performance and educational quality.